Experiences with budget rules in Switzerland and Germany - Karl Heinz Hausner; Silvia Simon (Intereconomics, 2015)
The Swiss debt brake served as a model for the new German budget rule. The two tools share the long-term goal of rendering fiscal policy sustainable by stabilising nominal debt as well as the short-term goal of smoothing the economic cycle. Debt brakes thus act as an automatic stabiliser within the economic cycle, but their effect can be impaired over the long term if government spending falls as debt is reduced.
Keywords: 330; Haushaltskonsolidierung; Haushaltsdefizit; Öffentliche Schulden; Vergleich; Schweiz; Deutschland